THE FEATURES OF BUDGET FINANCING OF PRIORITY BRANCHES OF UKRAINE’S ECONOMY IN MODERN CONDITIONS - Shchur, R.I.; Plets, I.I.; Voytovych, I.I. (The actual problems of regional economy development, 2020)
The article the theoretical foundations of budget financing of priority brunches of the Ukrainian economy are investigated. The criteria for selecting priority economic sectors in terms of budget funding are emphasized. Studies of the current macroeconomic situation in Ukraine shows that government support is needed for the development of priority brunches of the economy. The analysis of financing of priority sectors of the economy shows that priority brunches of the economy are mainly supported at the expense of enterprises' own funds, as well as credit resources of banks, national innovation and investment funds, state local budgets, and other funds. The financing of economic sectors from the state budget of Ukraine for 2015-2019 is analyzed. The structure of capital expenditures of the state budget for 2015–2019 is analyzed. The analysis shows that during the analyzed period the capital expenditures of the consolidated budget were in average 2.9% of GDP (1.4% of GDP from the state budget) and there was a tendency to reduce their share, which is a negative phenomenon for the national economy. It is proved that the need for public funds is due to the reduction of purchasing power of the population, stimulating the development of scientific and technological progress, the introduction of innovations, supporting the development of strategic and priority brunches of the economy.The main directions of further development of priority brunches of the economy and improvement of the investment environment in Ukraine based on improving the legal and organizational framework in order to increase the efficiency of the mechanism for ensuring a favorable investment environment, improving the competitiveness of the national economy, balancing the structure of budget expenditures, increasing share of project cost.